Changes in the gendered nature of homicides: comparing 20th- and 21st-century Finland - Virtanen, Suvi (European journal of criminology, 2017)
Women commit fewer homicides than men, yet recent research has suggested that the nature of female-perpetrated homicides has started to resemble that of male perpetration. This study examines gender differences and changes in the nature of female and male homicides, and aims to demonstrate how developments in Finnish society, such as the formation of the welfare state, are reflected in the gendered nature of homicide offending. Data consist of samples from the early 20th and 21st centuries. Comparisons in frequencies are made concerning the profiles of the victim and the offender, as well as the context of the crime. Results indicate that female offending is more similar to male offending in the 21st century than it was in the early 20th century.